Natural and cultural landscapes in the province of Luya, Amazonas Department - Comeca Chuquipul, Miguel Ángel (2015)
Luya’s province, department of the Amazon, is located in the northeastern side of the Peruvian territory. It possesses a great variety of natural landscapes, as cataracts, vegetation, diversity of reliefs, ecological floors, as well as also cultural landscapes expressed in numerous archaeological remains, as Fortaleza Kuelap, sarchofagi, complexes habitacionales, many of them still not known by the scientific community due to the scanty realized local investigations. Nevertheless, the latter years they are increasing tourist visits, increased the pressure towards the landscape resources and that in the future put in risk his force. It is this sense that the present investigation tries to evaluate, to identify, to inventory, to describe and to locate geographically diverse natural landscape and culture in order to make known to the scientific community, population and relevant authorities to boost their preservation, conservation and sustainable use.